The NFL : Critical and Cultural Perspectives - Furness, Zack; Oates, Thomas Patrick (Book collections on Project MUSE., 2014)
"The National Football League is one of the most significant cultural engines in contemporary American life. Yet despite intense and near ubiquitous media coverage, commentators rarely turn a critical lens on the league to ask what material and social forces have contributed to its success, and how the NFL has influenced public life in the United States. The editors of and contributors to The NFL examine the league as a culturally, economically, and politically powerful presence in American life. The essays, by established and up-and-coming scholars, explore how the NFL is packaged for commercial consumption, the league's influence on American identity, and its relationship to state and cultural militarism. The NFL is the first collection of critical essays to focus attention on the NFL as a cultural force. It boldly moves beyond popular celebrations of the sport and toward a fuller understanding of football's role in shaping contemporary sport, media, and everyday life. Contributors include: David L. Andrews, Aaron Baker, Michael Butterworth, Jacob Dittmer, Dan Grano, Samantha King, Kyle Kusz, Toby Miller, Ronald L. Mower, Dylan Mulvin, Oliver J.C. Rick, Katie Rodgers, and the editors."--